ABORSI DALAM AL-QUR’AN QS. AL-ISRA’: 31 PERSPEKTIF TAFSIR AL-MISHBAH - Harika Dzunnuroin; Ahmad Muwafiq; Ridho, Ainur Ridho (JURNAL ILMU AL-QUR'AN DAN TAFSIR NURUL ISLAM SUMENEP, 2025)
Abstract Abortion cases are one of the real examples that occur in society. It is undeniable that human life today seems to be surrounded by crime. This reality, in addition to generating widespread anxiety about criminal acts, also triggers a sense of frustration among some segments of society, leading them to take justice into their own hands in response to immoral or criminal acts. The purpose of this study is to describe and examine the issue of abortion in the Qur’an, specifically in Surah Al-Isra’ [17]: 31, from the perspective of Tafsir Al-Mishbah. This research aims to explore how M. Quraish Shihab interprets Surah Al-Isra’, verse 31, as well as his view on the issue of abortion in the Qur’an. The method used in this study is library research, which involves collecting data through a review of theories and interpretations from various books, classical texts, and other relevant sources. From the results of this study, it can be revealed that the issue of the prohibition and permissibility of abortion still requires more detailed clarification from Islamic scholars. This need is particularly urgent because the permissibility granted by Islam is sometimes misinterpreted or misused by irresponsible individuals. Keywords: Abortion, Qur’an, Tafsir Al-Mishbah.